KEEFEKTIFAN PENGEMBANGAN MEDIA PEMBELAJARAN JEDA (JENDELA DAUN) PADA PEMBELAJARAN IPA SD MATERI JENIS DAN BENTUK TULANG DAUN TUMBUHAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV - Ilmi Puspitasari; Karimatus Saidah; Kukuh Andri Aka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by the results of observations and interviews conducted at SDN Klanderan, which showed that science learning was related to the learning outcomes of the shapes and types of plant leaf bones in class IV. The problems found are 1) students' lack of understanding regarding the material, shapes and types of plant leaf bones 2) students' conditions that are not conducive to learning 3) lack of teacher creativity in delivering learning 4) unavailability of learning media to support student learning 5) results Student learning regarding the shape and types of plant leaf bones is not optimal. The aim of this research is to determine the validity, practicality and effectiveness of the Daun Daun (JEDA) media development. This research uses the RnD (Research and Development) method. The model used in this research is ADDIE with stages, namely, 1) development stage, 2) design stage, 3) development stage, 4 ) implementation (implementation), evaluation (evaluation) stages. The subjects in this study used 2 schools, namely SDN Klanderand and SDN Plosolor with the number of students in each school being 18 and 23 students. Data collection techniques used in this research include structured interviews, questionnaires, observations and tests. The instruments used in this research were questionnaires, interview guidelines, observation guidelines and questions. The data analysis technique used is to determine the effectiveness of the product. Effectiveness can be seen from the score of students' learning completion results during the extensive test. After analyzing the data on the effectiveness test, they got a score of 97% based on the results of calculating the students' classical learning completeness which was carried out during the extensive test so it was categorized as very effective. Based on the analysis presented above, it can be concluded that the Leaf Window (JEDA) media is very effective so that it can be used in learning material about the shape and types of plant leaf bones in class IV.